2005
DOI: 10.1002/yea.1304
|View full text |Cite
|
Sign up to set email alerts
|

Influence of volatile compounds produced by yeasts predominant during processing of Coffea arabica in East Africa on growth and ochratoxin A (OTA) production by Aspergillus ochraceus

Abstract: The effects of volatile compounds produced during coffee processing by Pichia anomala, P. kluyveri and Hanseniaspora uvarum on growth of Aspergillus ochraceus and production of ochratoxin A (OTA) were studied. On malt extract agar (MEA) and on coffee agar (CA), exposure of A. ochraceus to the gaseous phase of malt yeast glucose peptone (MYGP) plates inoculated with P. anomala, P. kluyveri and H. uvarum inhibited fungal growth, with the two Pichia spp. showing the strongest effect. The main esters and alcohols … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
57
0
3

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 101 publications
(67 citation statements)
references
References 31 publications
3
57
0
3
Order By: Relevance
“…Yeast Pichia anomala inhibited OTA production by one isolate of P. verrucosum in malt extract agar medium as well as in wheat (Petersson et al 1998). Masoud et al (2005) found that Pichia anomala and Pichia kluyveri inhibited the production of OTA by A. ochraceus on malt extract agar medium and on coffee agar medium. According to Valero et al (2007b), the amount of OTA was reduced in healthy grapes during its dehydration when OTA-nonproducing A. niger aggregate was added to the inoculum of OTA-producing A. carbonarius.…”
Section: Prevention Of Ochratoxin a Contaminationmentioning
confidence: 91%
“…Yeast Pichia anomala inhibited OTA production by one isolate of P. verrucosum in malt extract agar medium as well as in wheat (Petersson et al 1998). Masoud et al (2005) found that Pichia anomala and Pichia kluyveri inhibited the production of OTA by A. ochraceus on malt extract agar medium and on coffee agar medium. According to Valero et al (2007b), the amount of OTA was reduced in healthy grapes during its dehydration when OTA-nonproducing A. niger aggregate was added to the inoculum of OTA-producing A. carbonarius.…”
Section: Prevention Of Ochratoxin a Contaminationmentioning
confidence: 91%
“…Previously, higher mold incidence in cherry coffee has been reported by several researchers (Batista et al 2009;Taniwaki et al 2003;Velmourougane et al 2010b). Various types of yeast species are reported to inhibit molds (Wisniewski et al 1991;Paster et al 1993;Petersson et al 1998;Grieco et al 2006;Shetty and Jespersen 2006) and specifically, species of Pichia and Hanseniaspora genera have been shown to act as biocontrol agents against A. ochraceus (Masoud et al 2005;Masoud and Kaltoft 2006). Reductions of OTA by yeast species have been achieved by the ability to adsorb or to retain mycotoxins (Garcia-Moruno et al 2005).…”
Section: Delay In Processing On Mold Incidence In Coffeementioning
confidence: 95%
“…The work of Masoud et al and Masoud and Kaltoft points at another potential use of arti fi cial inoculation of cocoa fermentations, as strains of Pichia anomala , P. kluyveri, and H. uvarum isolated from coffee fermentations have been found to inhibit growth and ochratoxin A production by Aspergillus ochraceus [ 116,117 ] . The primary processing of cocoa and coffee has a number of similarities [ 117 ] , and it is indeed possible that the potential of some yeasts to inhibit mold growth and mycotoxin production could be exploited in the primary processing of cocoa as well.…”
Section: Use Of Starter Cultures For Fermentation Of Cocoamentioning
confidence: 97%